PENGARUH KUALITAS LAYANAN, KEPUASAN NASABAH DAN CITRA PERUSAHAAN TERHADAP LOYALITAS NASABAH PT. BANK CENTRAL ASIA TBK KANTOR CABANG PONDOK GEDE PLAZA - Puteri Herlanie Susanto; Iwan Kurniawan Subagja (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2019)
This study aims to investigate whether there is an influence of service quality on customer loyalty, determine whether there is an influence of customer satisfaction on customer loyalty, find out if there is partial effect between corporate image on customer loyalty and determine whether there are influence service quality, customer satisfaction and corporate image of the customer loyalty. Study sample in this research is 60 a sample and the technical sampling using incidental sampling. Analysis of data using multiple linear regression. The analysis showed that the effect of service quality on customer loyalty and has a significant relationship, customer satisfaction variables found to influence positive but not significant and the Corporate's image variables showed no effect on customer loyalty. Variable quality of service, customer satisfaction, and corporate image have influence and have a significant level of good relationship on customer loyalty.